2012
DOI: 10.1128/aac.00407-12
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Helicobacter pylori Potential of Artemisinin and Its Derivatives

Abstract: ABSTRACTThe antimalarial drug artemisinin fromArtemisia annuademonstrated remarkably strong activity againstHelicobacter pylori, the pathogen responsible for peptic ulcer diseases. In an effort to develop a novel ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…A good practice in diagnosing H. pylori with antigen tests is that antibiotics should be stopped at least four weeks and anti-secretory therapy at least two weeks before testing, as these medications negatively affects the sensitivity [11]. In Mali malaria is endemic, and antimalaria drugs might have a negative effect on the sensitivity of the test, as these drugs might eradicate or decrease the presence of H. pylori [17,18]. Most of the individuals in our study have a low educational level, and it was therefore difficult to know if they had been taking any interfering medications.…”
Section: Discussionmentioning
confidence: 99%
“…A good practice in diagnosing H. pylori with antigen tests is that antibiotics should be stopped at least four weeks and anti-secretory therapy at least two weeks before testing, as these medications negatively affects the sensitivity [11]. In Mali malaria is endemic, and antimalaria drugs might have a negative effect on the sensitivity of the test, as these drugs might eradicate or decrease the presence of H. pylori [17,18]. Most of the individuals in our study have a low educational level, and it was therefore difficult to know if they had been taking any interfering medications.…”
Section: Discussionmentioning
confidence: 99%
“…In a set of eleven studies [45][46][47][48][49][50][51][52][53][54][55] determining an activity and morphological effect of plant extracts and plant-derived compounds on H. pylori, four of them reported a bacteriostatic activity [45][46][47][48] and six indicated a bactericidal effect [49][50][51][52][53][54] of the tested compounds. In one case, the use of this classification was avoided [55].…”
Section: Plant Extracts and Plant-derived Compoundsmentioning
confidence: 99%
“…The six studies indicated the bactericidal effect of the tested compounds on H. pylori [49][50][51][52][53][54]. A capacity to completely inhibit growth was only proven in half of them [49,51,52], which was achieved in a range of 18 h [49] to 72 h [51] with MICs. A relationship between the decrease in viability and number of spherical forms was particularly well illustrated in the Lee et al article [51].…”
Section: Plant Extracts and Plant-derived Compoundsmentioning
confidence: 99%
“…A good practice in diagnosing H. pylori with antigen tests is that antibiotics should be stopped at least four weeks and anti-secretory therapy at least two weeks before testing, as these medications negatively affects the sensitivity [11]. In Mali malaria is endemic, and anti-malaria drugs might have a negative effect on the sensitivity of the test, as these drugs might eradicate or decrease the presence of H. pylori [17, 18]. Most of the individuals in our study have a low educational level, and it was therefore difficult to know if they had been taking any interfering medications.…”
Section: Discussionmentioning
confidence: 99%